Analisa Stabilitas Sistem Kelistrikan Sumatera dengan Beroperasinya PLTGU Riau 275 MW menggunakan Simulasi Digsilent - Yolnasdi, Yolnasdi; Waskito, Lilik Anggit; Setiawan, David (SainETIn : Jurnal Sains, Energi, Teknologi, dan Industri, 2021)
Sumatra's electricity system is the second largest in Indonesia after the Java-Bali electricity system. According to the 2019-2028 RUPTL (General Plan for Electricity Concession) in the Sumatra system, in Riau province, the IPP PLTGU Riau 275 MW plant will operate in 2021. the inclusion of the Riau 275 MW PLTGU plant in the system, in addition to increasing the power supply, will also affect stability. Sumatra electricity. the analysis is needed to see the reliability of the system when a disturbance occurs. The observed stability is the stability of the voltage and frequency as a result of the trip generator disturbance. Several scenarios were carried out to see frequency stability by tripling several generating units until the system stability limit was exceeded. To overcome the frequency stability disturbance, a low-frequency load release scheme (UFLS) is carried out so that the system can maintain its stability. In this study, Digsilent 15 software was used to run the simulation. The simulation results show that when the Riau 275 MW PLTGU is already operating and there is a disturbance in the system, the frequency response of the system is better than when the unit is not yet operating. In the fault scenario of 4 generating units (411 MW) trip, the system stability limit is exceeded, so it is necessary to carry out a load shedding scheme (UFLS) to maintain its stability. The implementation of the UFLS scheme when the Riau 275 MW PLTGU was already operating provided a saving of 73.47 MW or the equivalent of Rp. 106,142,109.00 per hour